Fine needle aspiration cytology of breast lesions and correlation with histopathology - Waghmare, Ramesh S.; Sakore, Shubhangi D.; Rathod, S. B. (International Journal of Research in Medical Sciences, 2016)
Background: Breast carcinoma is the leading cause of death due to cancer in women. It is difficult to determine whether a lump is benign or malignant from clinical assessment. Fine needle aspiration cytology (FNAC) is a convenient and rapid procedure. Hence the present study was carried out to correlate fine needle aspiration cytology and histopathology of breast lesions. Methods: A study consisting of fine needle aspiration cytology (FNAC) 134 of breast lesions and their histopathological correlation was conducted at tertiary health center in rural area, over a period of three years. The diagnostic accuracy of this series was assessed and compared with data obtained from the Indian and international literature. Statistical analysis like sensitivity, specificity, positive predictive value, efficiency, and negative predictive value were carried out. Results: The diagnostic accuracy of this series i.e. sensitivity 88.24%, specificity 100%, positive predictive value 100%, efficiency 95.52%, and negative predictive value 93.2% was compared with similar studies in literature. Conclusions: FNAC is an effective modality for the diagnosis of breast lesions. It is a safe, simple, and cost effective outpatient procedure associated with negligible complications. It helps the clinicians for early diagnosis and specific management thus reducing morbidity and mortality.